Pengaruh Insider Ownership dan Risiko Pasar terhadap Kebijakan Dividen - Suwaldiman Suwaldiman; Ahmad Aziz (Universitas Islam Indonesia, 2006)
This research tests the effect of insider ownership, market risk, market to book value, size, earning variability, profitability, and growth to the dividend policy represented by dividend pay-out ratio. Main independent variables and control independent variables are employed in this research. The main independent variables consist of insider ownership and market risk. Meanwhile, the control variables consist of market to book value, size, earning variability, profitability, and growth. The analysis of this research proves that the dividend policy does not depend on the amount of the share ownership by insider parties such as managers. Additionally, the dividend policy also does not depend on the market risk. Those mean that the bigger amount of share ownership by insiders and the higher market risk do not cause to the lower dividend payment represented by dividend pay-out ratio.Key words: insider ownership, market risk, market to book value, size, earning variability, profitability, dividend policy, dividend pay-out ratio.